The Challenges of Teaching Reading Using the Cooperative Integrated Reading and Composition (CIRC) Method - Illananingtyas, Tenika; Syahri, Zulkhoirian (TADBIR MUWAHHID, 2025)
Reading is one of the most fundamental language skills that students must master to succeed in education and beyond. Yet, teaching reading in formal education often encounters multiple obstacles, ranging from low student motivation to the dominance of teacher-centered approaches. To address these issues, Cooperative Integrated Reading and Composition (CIRC), a cooperative learning model that integrates reading and writing, has been widely introduced and tested. This article investigates the challenges faced by teachers in applying the CIRC method in the teaching of reading comprehension at MTs Negeri 4 Kediri, Indonesia. Using a qualitative descriptive design, the study collected data through observations, interviews, and documentation with teachers, students, and the school principal. The findings indicate that while CIRC enhances student engagement, collaboration, and comprehension, it also poses challenges such as time management, unequal participation among students, and adaptability issues during remote or pandemic learning. This paper discusses these challenges in light of previous research, theories of cooperative learning, and broader educational implications, while suggesting strategies for teachers and institutions to optimize the use of CIRC in diverse contexts.